Renewable energy Europe. A special report on the National Renewable Energy Action Plans outlining goals and measures to boost renewable energy use (London, 2010)
"This report aims to give a snapshot of EU plans to make the challenging transition towards renewable energy sources. We analysed National Renewable Energy Action Plans from: Austria, the Czech Republic, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Lithuania, Malta, Netherlands, Portugal, Slovenia, Spain, Sweden, UK. We also looked at nonsubmitted plans from Poland and Slovakia. This report includes data from Bulgaria, Cyprus and Luxembourg, while Belgium, Estonia, Hungary, Latvia and Romania are not included. All information is updated to 21 September 2010."